The role of treponema denticola in the periodontitis alveolar bone damage: a systematic review - Idrus, Erik; Hartanto, Willy; Lestari, Widya; Suniarti, Dewi Fatma (Faculty of Dentistry, Universitas Islam Sultan Agung, 2023)
ABSTRACT Background: Periodontitis is a chronic inflammation condition of the periodontal tissue, which causes irreversible, progressive deterioration of the tooth-supporting tissue, leading to tooth loss. One of the main bacteria in the pathogenesis of periodontitis is Treponema denticola. Its involvement in periodontitis includes producing and releasing various virulence factors that further modulate inflammation and ignite alveolar bone destruction.To examine Treponema denticola's role in the mechanism of alveolar bone damage in periodontitis. Method: This systematic review was conducted from August 2021 until April 2022. Qualified literature is evaluated based on inclusion criteria, including published in English within the last ten years and research articles available in full text. The inclusion literature’s determination was based on the PRISMA (Preferred Reporting Item for Systematic Review and Meta-Analysis). Result: Six journals fit the inclusion criteria and discuss Treponema denticola involvement in alveolar bone destruction via several mechanisms, including periplasmic flagella as its virulence factor. Treponema denticola can inhibit osteogenic cell differentiation and induce the production TNF-α, IL-6, and IL1β, which are the proinflammatory cytokines involved in osteoclastogenesis. The induction mechanism of these various cytokines can ultimately increase osteoclast differentiation by increasing RANKL expression and decreasing OPG expression. Conclusion: Treponema denticola is involved in alveolar bone destruction by inhibiting bone formation and inducing an inflammatory response in immune cells that can increase osteoclast differentiation, as observed in alveolar bone destruction.